Store choice in the Emerging Indian apparel retail market: An empirical analysis - Amit Mittal; Ruchi Mittal (IBSU Scientific Journal (IBSUSJ), 2008)
Store Choice has been a subject of frequent research in the developed retail markets of the west. However, the retail sector in India has been largely fragmented and unorganized. However, the retail scenario in India is changing at a very brisk pace. Many international retailers entering India and many Indian retailers in the organized segment are coming up with stores all across the western formats onto the Indian retail scene without actually evaluating the salience of various store attributes from the customer perspective. In light of this the purpose of this paper is to study the store choice criteria in the context of apparel retailing in India. Drawing from major global and Indian studies conducted in the past, this research has identified two dimensions, which in different combinations could create sustainable store choice and hence, store loyalty. These two dimensions are termed loyalty drivers and experience enhancers.
Keywords: 330; store choice; store image; store attributes; shoppers' loyalty; apparel retailing; factor analysis